Supplemental Material, sj-pdf-1-ang-10.1177_0003319720987351 - Cardiac Catheterizations in Patients With Prior Coronary Bypass Surgery: Impact of Access Strategy on Short-Term Safety and Long-Term Efficacy Outcomes - Frederik T. Groenland (10010054); Jeroen M. Wilschut (10010057); Stijn C. van den Oord (10010060); Isabella Kardys (817218); Roberto Diletti (10010063); Peter P. de Jaegere (10010066); Felix Zijlstra (20678); Joost Daemen (5474747); Nicolas M. Van Mieghem (6925160); Wijnand K. den Dekker (10010069) (2021)
Supplemental Material, sj-pdf-1-ang-10.1177_0003319720987351 for Cardiac Catheterizations in Patients With Prior Coronary Bypass Surgery: Impact of Access Strategy on Short-Term Safety and Long-Term Efficacy Outcomes by Frederik T. Groenland, Jeroen M. Wilschut, Stijn C. van den Oord, Isabella Kardys, Roberto Diletti, Peter P. de Jaegere, Felix Zijlstra, Joost Daemen, Nicolas M. Van Mieghem and Wijnand K. den Dekker in Angiology